Endoscopic prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis - Lee, Tae Hoon (World J Gastroenterol, 2014)
Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is not an uncommon adverse event but may be an avoidable complication. Although pancreatitis of severe grade is reported in 0.1%-0.5% of ERCP patients, a serious clinical course may be lethal. For prevention of severe PEP, patient risk stratification, appropriate selection of patients using noninvasive diagnostic imaging methods such as magnetic resonance cholangiopancreatography or endoscopic ultrasonography (EUS), and avoidance of unnecessary invasive procedures, are important measures to be taken before any procedure. Pharmacological prevention is also commonly attempted but is usually ineffective. No ideal agent has not yet been found and the available data conflict. Currently, rectal non-steroidal anti-inflammatory drugs are used to prevent PEP in high-risk patients, but additional studies using larger numbers of subjects are necessary to confirm any prophylactic effect. In this review, we focus on endoscopic procedures seeking to prevent or decrease the severity of PEP. Among various cannulation methods, wire-guided cannulation, precut fistulotomy, and transpancreatic septostomy are reviewed. Prophylactic pancreatic stent placement, which is the best-known prophylactic method, is reviewed with reference to the ideal stent type, adequate duration of stent placement, and stent-related complications. Finally, we comment on other treatment alternatives, and make the point that further advances in EUS-guided techniques may afford useful PEP prophylaxis.